Physiotherapist Factors Associated With the Intention to Deliver Psychologically Informed Physiotherapy in Persistent Low Back Pain: A Vignette Study - Earl, Claire (Auckland University of Technology, 2025)
Introduction Non-specific low back pain is a leading cause of disability worldwide and can have devastating impacts on work, whānau and community roles, social relationships and quality of life. Physiotherapists are the main providers of low back pain care in Aotearoa New Zealand, so supporting them to provide evidence based, and effective management is crucial to improve pain outcomes. Psychologically informed physiotherapy (PIP) incorporates the use of psychological techniques within physiotherapy. PIP can improve pain outcomes compared to usual physiotherapy, but global research suggests that many physiotherapists do not provide PIP in real life clinical practice. It is not known how many New Zealand physiotherapists provide PIP to people with low back pain. Qualitative research suggests the barriers to delivering PIP are related to physiotherapists’ confidence, knowledge, skills, lack of time, biomedical orientation, organisational support, training and supervision. The relative importance of these barriers has not been evaluated quantitatively. Aims This study aimed to determine the proportion of physiotherapists in Aotearoa New Zealand that intend to deliver PIP to patients with persistent low back pain, and identify which factors are associated with the intention to deliver PIP. Methods New Zealand physiotherapists (n = 224) completed an online vignette case study where they outlined their intended assessment and treatment plan for two persons with persistent low back pain. They then completed the Knowledge and Attitudes of Pain Questionnaire (KNAP), components of the Determinants of Implementation Behaviour Questionnaire (DIBQ) and demographic questions. Logistic regression was used to determine which questionnaire and demographic variables were associated with the intention to deliver PIP. Results One third of participants intended to deliver PIP in the management of low back pain. A logistic regression analysis showed that the KNAP score was consistently and most strongly associated with the intention to deliver PIP. Beliefs about the consequences of PIP was also associated with the intention to deliver PIP in one vignette. Conclusion This study suggests that physiotherapists’ knowledge and attitudes towards pain and their belief that PIP is effective in low back pain management are associated with PIP delivery in Aotearoa New Zealand. These findings indicate that improving pain knowledge and beliefs around PIP may improve the quality of low back pain management. Future research needs to confirm these results in clinical settings, understand how pain neuroscience knowledge is acquired, and identify how best to translate this into Aotearoa New Zealand physiotherapy practice.